Relationship Between Pre Menstrual Syndrome With Body Mass Index Among University Students - Vahideh Shirazi; Mohammad Asghari Jafarabadi; Fereshteh Narenji; Tooba Heidari; Leila Amiri Farahani (Tehran University of Medical Sciences, 2011)
Background & Aim: Several factors have been reported to be influential in development of the premenstrual syndrome. There are no studies available on relationship between premenstrual syndrome with body mass index in Iran. This study aimed to determine this relationship among university students.Methods & Materials: This was a cross-sectional study conducted on a random sample of 500 students living in the dorms of Arak University of Medical Sciences. The participants had not stress, anxiety and severe depression on the basis of the DASS21. Data were gathered using Social Status Questionnaire, including demographic, menstrual status, reproductive and eating habits and body mass index measurement items. The participants completed the abbreviated form of premenstrual syndrome evaluation within seven days of bleeding up to two days after onset of bleeding for one cycle. Using logistic regression analysis, the association was assessed by adjusting for confounding variables.Results: A majority of the students had normal BMI (<25) (90.8%). The results showed that the risk of premenstrual syndrome in the participants with high BMI was 2.43 times more than the participants with normal BMI (OR=2.43; CI=8.33-1.66).Conclusion: High BMI increased the risk of premenstrual syndrome. Interventions to decrease the BMI should be designed and implemented in overweight and obese patients with premenstrual syndrome.